2019
DOI: 10.1097/md.0000000000016972
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs10204525 genotype GG and rs2227982 CC combination in programmed cell death 1 with hepatitis B virus infection risk

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A number of SNPs have been identified that may alter the expression and function of PD-1, with reports linking these to autoimmune disease [ 59 ], but also immunosuppressive conditions. PDCD1 rs10204525 C > T is located at the 3′UTR, increasing PD-1 expression and reportedly promoting dysfunctional T cell responses and persistence in HBV infection [ 26 , 27 , 28 , 29 , 30 , 31 , 33 , 60 ]. The promotion of an immunosuppressive phenotype by PDCD1 rs10204525 C > T may also contribute to tumour development but has not as yet been characterised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of SNPs have been identified that may alter the expression and function of PD-1, with reports linking these to autoimmune disease [ 59 ], but also immunosuppressive conditions. PDCD1 rs10204525 C > T is located at the 3′UTR, increasing PD-1 expression and reportedly promoting dysfunctional T cell responses and persistence in HBV infection [ 26 , 27 , 28 , 29 , 30 , 31 , 33 , 60 ]. The promotion of an immunosuppressive phenotype by PDCD1 rs10204525 C > T may also contribute to tumour development but has not as yet been characterised.…”
Section: Discussionmentioning
confidence: 99%
“…Here, in the hope of enhancing our understanding of NAFLD-HCC in a clinically translatable fashion, we have explored SNPs in a number of candidate HCC immunoregulatory genes, in addition to those in PNPLA3 and TM6SF2 , in patients with NAFLD and NAFLD-HCC. The SNPs selected were based on previous reports and included rs2596542 in Major Histocompatibility Complex class I polypeptide related sequence A ( MICA ) [ 19 ], rs187115 in Cluster of differentiation 44 ( CD44 ) [ 20 , 21 , 22 ], as well as rs7421861 and rs10204525 in programmed cell death-1 ( PDCD1 ) which encodes PD-1 [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. PDCD1 rs10204525 C < T is common in Asian populations, with functional implications for patients with HBV.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] revealed no significant association between PD-1 rs36084323 polymorphism and overall cancer susceptibility. Rs2227982 was demonstrated to be associated with the risk and disease progression of SLE, allergic bronchial asthma, AS, breast cancer, and gastric and digestive system cancers, such as adenocarcinoma, in previous reports [ 13 , 21 ]. A recent study indicated a significant association between rs2227982 and HBV infection as well as a gene–gene interaction with rs10204525 in a Chinese population [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rs2227982 was demonstrated to be associated with the risk and disease progression of SLE, allergic bronchial asthma, AS, breast cancer, and gastric and digestive system cancers, such as adenocarcinoma, in previous reports [ 13 , 21 ]. A recent study indicated a significant association between rs2227982 and HBV infection as well as a gene–gene interaction with rs10204525 in a Chinese population [ 21 ]. On the contrary, a meta-analysis involving 12 case–control studies revealed no associations between cancer risks and rs2227982 in all genetic models and alleles [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation